Social licence to operate: understanding how a concept has been translated into practice in energy industries. (1st January 2015) - Hall, Nina; Lacey, Justine; Carr-Cornish, Simone; Dowd, Anne-Maree
Abstract: The emergence of the 'social licence to operate' concept reflects increasing awareness by industries of the need to negotiate with communities and other stakeholders regarding the costs and benefits associated with industrial development. It has been assumed that all industries understand and apply the social licence to operate concept in a similar way, as previous research has tended to adopt a single-industry focus. This article is one of the first known cross-industry examinations of social licence to operate, comparing the use of this concept in four Australian energy industry contexts: mining, wind, carbon dioxide capture and storage, and geothermal. Semi-structured interviews with industry representatives were conducted to provide a comparison of views on the understanding and application of social licence to operate in these industries. The findings identified shared expectations of increasing stakeholder engagement in energy project development, and a view that a social licence to operate could guide this engagement. Yet the duration of use, the maturity of the industry, and the ways in which the industries related to the concept influenced the understanding and application of this concept. This research provides evidence of how the meaning and application of social licence to operate does vary between industries. Further exploration of community and government perspectives on social licence to operate is recommended in order to broaden the findings of this research. Such research will provide an emerging platform for encouraging discerning use of the concept by industries, and also practitioners who may be engaged across multiple industries. Highlights: 'Social licence to operate' reflects increasing awareness of community engagement. This is one of the first known cross-industry comparisons of SLO. Understanding and experience of SLO influences industry's application. SLO requires clarification in each context to avoid misinterpretation. The energy industry anticipates increased stakeholder engagement in energy projects.